2018
DOI: 10.5194/essd-2017-138
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Seasonal Carbonate Chemistry Variability in Marine Surface Waters of the Pacific Northwest

Abstract: Abstract. Fingerprinting ocean acidification (OA) in U.S. West Coast waters is extremely challenging due to the large magnitude of natural carbonate chemistry variations common to these regions. Additionally, quantifying a change requires information about the initial conditions, which is not readily available in most coastal systems. In an effort to address this issue, we have collated high-quality, publicly-available data to characterize the modern seasonal carbonate chemistry variability in marine surface w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Net calcification has been confirmed by independent assessments at some of these coral reef time series stations (Bates et al, 2010;Courtney et al, 2016;Drupp et al, 2011;Shamberger et al, 2011). which experiences greater water residence time and more persistent stratification, and therefore, increased influence of biological production and respiration on seawater xCO2 (Fassbender et al, 2018;Lindquist et al, 2017). These processes can cause subsurface hypoxia and low pH (<7.4) and aragonite saturation (<0.6) conditions in this region of Puget Sound (Feely et al, 2010) the offshore stations of WHOTS and BTM both exhibit climatological mean seawater pCO2 slightly below atmospheric values (Fig.…”
Section: Climatology and Natural Variabilitymentioning
confidence: 83%
See 1 more Smart Citation
“…Net calcification has been confirmed by independent assessments at some of these coral reef time series stations (Bates et al, 2010;Courtney et al, 2016;Drupp et al, 2011;Shamberger et al, 2011). which experiences greater water residence time and more persistent stratification, and therefore, increased influence of biological production and respiration on seawater xCO2 (Fassbender et al, 2018;Lindquist et al, 2017). These processes can cause subsurface hypoxia and low pH (<7.4) and aragonite saturation (<0.6) conditions in this region of Puget Sound (Feely et al, 2010) the offshore stations of WHOTS and BTM both exhibit climatological mean seawater pCO2 slightly below atmospheric values (Fig.…”
Section: Climatology and Natural Variabilitymentioning
confidence: 83%
“…The coastal time series stations 25 suggest annual CO2 uptake with climatological means of seawater pCO2 less than atmospheric CO2 levels. Seasonal changes of SST and biological productivity drive the large seasonal amplitudes in pCO2 and pH at the U.S. coastal locations (Fassbender et al, 2018;Reimer et al, 2017;Sutton et al, 2016;Xue et al, 2016). The coastal stations Twanoh and Coastal MS exhibit the highest IAV of seawater pCO2 (reported as seawater xCO2 for Twanoh) due to large variability from year to year in circulation, freshwater input, and biological productivity (Fig.…”
Section: Climatology and Natural Variabilitymentioning
confidence: 99%
“…The coastal time series stations suggest annual CO2 uptake with climatological seawater pCO2 means less than atmospheric CO2 levels. Seasonal changes of SST and biological productivity drive the large seasonal amplitudes in pCO2 and pH at the U.S. coastal locations (Fassbender et al, 2018;Reimer et al, 2017;Sutton et al, 2016;Xue et al, 2016). The coastal stations Twanoh and Coastal MS exhibit the highest 10 IAV of seawater pCO2 (reported as seawater xCO2 for Twanoh) due to large variability from year to year in freshwater input and biological productivity ( Fig.…”
Section: Climatology and Natural Variabilitymentioning
confidence: 99%
“…Seasonal variability and IAV are almost twice as large at the time series stations within the freshwater-influenced Puget Sound (Dabob and Twanoh) compared to the stations on the outer coast of Washington (Chá bă and Cape Elizabeth). Dabob is closer to the inlet of Puget Sound compared to Twanoh, which experiences greater water residence time and, therefore, greater influence of biological production and respiration on seawater xCO2(Fassbender et al, 2018; Lindquist et al, 2017). These processes can cause subsurface hypoxia and low pH (<7.4) and aragonite 20 saturation (<0.6) conditions in this region of Puget Sound(Feely et al, 2010), which likely contribute to the elevated surface seawater xCO2 levels observed at Dabob and Twanoh.…”
mentioning
confidence: 99%